The impact of aneurysm volume on midterm Post-EVAR outcomes - Mehmet Ali Turkcu; Osman Eren Karpuzoglu; Bahadir Aytekin; Ferit Cetinkaya; Mustafa Dagli; Hakki Zafer Iscan (Turkish Journal of Vascular Surgery)
Aim: We examined the impact of preoperative three-dimensional aortic volume on outcomes following Endovascular Aortic Repair (EVAR). Material and Methods: A total of 146 patients who underwent elective EVAR at our hospital between January 2018 and January 2023, and who had preoperative and postoperative multislice Computed Tomographic Angiography (CTA), were included in the study. The effects of aneurysm sac volumetric measurements on post-EVAR endoleak, reintervention, and late mortality were evaluated. Since there is no definite cut-off value for aneurysm volume and EVAR results in the literature, we compared patients with aneurysm volumes above and below 231.7 cm³ obtained by roc analysis. Results: During the follow-up period, the rate of secondary intervention was higher if the preoperative aneurysm volume was greater than 231.7 cm³ (p=0.001) or if the preoperative thrombus volume was greater than 206.1 cm³ (p=0.002). There was no notable difference in terms of endoleak (p=0.5) and during follow-up mortality rate (p=0.8) between patients with sac volumes above and below 231.7 cm³. After EVAR, when morphological changes were examined, it was noted that there was a dilatation of the neck (preoperative 23±4 mm and postoperative 26±4 mm) (p [Turk J Vasc Surg 2024; 33(2.000): 78-83]